Improvement of alfalfa resistance against Cd stress through rhizobia and arbuscular mycorrhiza fungi co-inoculation in Cd-contaminated soil - Wang, Xia; Fang, Linchuan; Beiyuan, Jingzi; Cui, Yongxing; Peng, Qi; Zhu, Shilei; Wang, Man; Zhang, Xingchang (Environmental pollution (1987), 2021)
Rhizobia and arbuscular mycorrhiza fungi (AMF) are important symbiotic microbes that are advantageous to plants growing in metal-contaminated soil. However, it remains unclear how inoculated microbes affect rhizosphere microbial communities or whether subsequent changes in rhizosphere microbiomes contribute to improving plant resistance under metal stress. This study investigated the effects of rhizobia and AMF inoculation on alfalfa resistance to Cd stress. The response of rhizosphere microbial communities to inoculation and its role in increasing alfalfa’ ability to cope with stress were further analyzed using high-throughput sequencing of 16S and ITS rRNA genes. Results showed that single rhizobia or AMF inoculation significantly improved alfalfa resistance to Cd stress, while their co-inoculation resulted in the greatest overall improvement. Improved resistance was reflected by the significant mitigation of Cd-induced lipid peroxidation and reactive oxygen species (ROS) stress caused by increases in antioxidant enzyme activities along with co-inoculation. Furthermore, co-inoculation significantly altered the rhizosphere microbial community structure by decreasing fungal community diversity and increasing bacterial community diversity. Results of partial least squares path modeling (PLS-PM) and variation partitioning analysis (VPA) showed that the rhizosphere bacterial community predominated over the fungal community with respected to improvements in resistance to Cd stress under the co-inoculation treatments. This improvement was specifically seen in the enrichment of certain key bacterial taxa (including Proteobacteria, Actinobacteria, Acidobacteria, and Chloroflexi) induced by the rhizobia and AMF co-inoculation, enhancing alfalfa’ ability to uptake rhizosphere nutrients and reduce its release of photosynthetically-derived carbon (C) into soil. Our findings revealed that the co-inoculation of multiple symbiotic microbes can assist plants to effectively cope with Cd stress, providing a greater understanding of rhizosphere bacterial taxa in the microbe-induced phytomanagement. [Display omitted] •Co-inoculation maximized the plant resistance to Cd stress.•Alpha diversity of rhizosphere bacteria and fungi reversely responded to inoculation.•Bacterial taxa change induced by inoculation determined plant resistance improvement.•Bacterial indicator species in rhizosphere regulated plant to take up nutrients. Rhizobia and AMF co-inoculation can alter key bacterial taxa of rhizosphere soil and enhance alfalfa to uptake nutrients, which improves plant resistance to Cd stress.